Understanding Consumer Switching Intention to Digital Banks: An Empirical Test of Push-Pull-Mooring Framework - Anniza Citra Prajasari; Syayyidah Maftuhatul Jannah (Universitas Negeri Semarang, 2026)
This study examines the factors influencing consumers’ switching intention from traditional banking services to digital banks using the Push-Pull-Mooring (PPM) framework. Although the PPM framework is widely used in digital banking research, prior studies remain fragmented in their application and often rely on crosssectional surveys that primarily measure switching intention, limiting a comprehensive understanding of switching determinants. This study analyzes primary data collected through questionnaires from 610 respondents using purposive sampling, with 71% of respondents already using digital banks. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Pull Factors and Mooring Factors have a significant positive effect on individuals’ intention to adopt digital banks, while Push Factors have no significant effect. These findings suggest that the attractiveness of digital banking services and personal considerations play important roles in encouraging digital bank adoption. Strengthening public literacy, branding, and digital security assurance is recommended to accelerate adoption.